Job placement in Europe: An international comparison - Ulrich Walwei (Intereconomics, 1991)
The role of private employment agencies in job placement has increased in importance in many European countries during the last decade, but in others the public employment services still exercise a monopoly. The following paper offers an assessment of the experiences to date.
Keywords: 330